ARTICLE REVIEW ABOUT THEORETICAL VIEWS ON THE CONCEPT OF SUSTAINABLE DEVELOPMENT - Eman Abdalkadhem Jabbar Al-kuraity; Huda Z. Miklif (Scholars Digest Publishing, 2025)
Sustainable development aims to strike a balance between satisfying the demands of current generations and safeguarding the capacity of future generations to fulfill their own. Three main aspects underpin this idea: an economy emphasizing sustainable growth via efficient resource use; an environment demanding natural resource conservation and pollution control; and a society supporting social justice and equal opportunity in education, health, and work. Introduced in the 1987 report our common future, this idea served as a cornerstone for grasping sustainable development and advocated development plans preserving natural resources for future generations. Theoretical approaches to sustainable development differ from economic theory, which links economic growth with environmental protection; social theory, which emphasizes achieving social justice and improving individual well-being; and environmental theory, which stresses protecting the environment from excessive depletion. Policies and practices of countries like Sweden and Denmark have also helped to emphasize the practical aspect of sustainable development by helping to create a balance between environmental preservation and economic growth. Good laws and policies also underline the need of institutions in fulfilling sustainable development goals. Some policies, therefore, draw criticism for giving the environment or the economic first priority at the cost of other facets of sustainable development. Sustainable development is an integrated process that ensures the sustainability of resources and the welfare of future generations by means of the interaction of various economic, social, and environmental elements.
Keywords: Sustainable development, economy, environmental, Theoretical.